Ethics and Law of Personal Data Protection for Smartwatches in the Healthcare Sector - Irwanto, Hartono Tasir; Wiranti, Wiranti; Dahlan, Muhammad Fitratallah; Kadir, Nadiah Khaeriah (CV. Social Politic Genius (SIGn), 2025)
The rapid adoption of smartwatches in the healthcare sector presents a fundamental duality between the potential for medical innovation and systemic risks to the right to privacy. This research aims to critically analyze the juridical-ethical gap between the health data governance practices of the smartwatch industry and the normative standards mandated by Law Number 27 of 2022. Using a normative legal research method and a gap analysis approach, this study dissects how industry practices systematically create a transparency deficit and devalue the meaning of informed consent into an illusory agreement. The analysis reveals a diametrical opposition between the regulatory ideal (das sollen), which prioritizes user autonomy, and the reality of industry practices (das sein), which are driven by commercial interests and formalistic compliance. This gap not only exposes users to data exploitation but also challenges the effectiveness of Law Number 27 of 2022 in addressing the complexity of wearable technology. Therefore, this research recommends a paradigm shift from the fragile consent-based model to a rights-based model. Furthermore, it urges the formulation of specific implementing regulations for the health technology sector to bridge the existing gap and build a fair and accountable digital ecosystem.